Pengaruh Teknik Rebozo Terhadap Tingkat Nyeri Kala I Pada Ibu Bersalin Primipara - awwalul wiladatil qodliyah (Jurnal Keperawatan Muhammadiyah, 2020)
Objective:   Labor is a natural condition that occurs in women and, in the process, can cause severe pain, and some women can also experience excruciating pain. Pain that maternity mothers cannot overcome can affect the mother's condition in the form of fatigue, frustration, hopelessness, and cause stress. Stress can cause the weakening of uterine contractions and result in prolonged labor. The Rebozo technique is a distraction technique that poses less risk or harmful side effects than pharmacological therapy. This study aimed to determine the effect of the rebozo technique on the length of the first stage and the pain level during labor at Practice Midwife Siti Nurul Aini.Methods: This study uses a pre-experimental research design. This study consisted of 2 groups: the treatment and control groups. The research was conducted from November 2019 to June 2020 at Practice Midwife Siti Nurul Aini. The population in this study were primigravida maternity mothers. The sample of this research was selected by using the purposive sampling technique. In this study, there were 16 respondents in the intervention group and 16 in the control group. The rebozo technique is given as long as there are contractions during the first stage of labor. The Verbal Descriptor Scale (VDS) measures the pain level. This study used an independent T-Test data analysis technique.Results: Based on the independent T-test, the P-value was 0.002, and less than 0.05, Ha was accepted, so it was concluded that the rebozo technique’s effect on the length of the first stage of labor. Statistical tests using the Independent T-test obtained a P-value of 0.000, less than 0.05, then Ha was accepted, concluding that the rebozo technique had affected the pain level in labor.Conclusion:   primigravida maternity who used the rebozo technique progressed faster than the control group. Meanwhile, the pain level of primigravida mothers who used the rebozo technique was lower than the control group. Therefore, the rebozo technique statistically affects the length of labor and the pain level in the first stage of labor in primiparous mothers. The results of this study can be used as an alternative non-pharmacological method in midwifery services to overcome labor pain.